UPAYA MENINGKATKAN KETERAMPILAN BERBAHASA MEMBACA KRITIS MELALUI MODEL PEMBELAJARAN MULTILITERASI KRITIS BERBASIS ENGAGED LEARNING PADA SISWA KELAS IV SDN BANYURADEN SLEMAN - Ika Saputri; Taufik Muhtarom (Berajah Journal, 2026)
The purpose of this study was to improve the critical reading skills of fourth-grade students of Banyuraden Public Elementary School through a critical multiliteracy learning model based on engaged learning. The research method used classroom action research with cycles 1 and 2. The study was conducted from November to December 2025, in Indonesian language lessons at Banyuraden Public Elementary School, Sleman Regency. The subjects were 30 fourth-grade students of Banyuraden Public Elementary School, Sleman Regency, studying Indonesian. Data collection methods included observation sheets, questionnaires, and test results. Data analysis techniques used were qualitative and quantitative analysis. The results of the study indicate that the average class score on the critical reading language skills test increased from pre-cycle (cycle I) to cycle II, with an average score of 60. In cycle 1, the average score increased from 72.89 to 81.11. In the pre-cycle, 5 students scored above the Minimum Competency (KKM) for critical reading skills, with a critical reading skills percentage of 16.67%. In cycle 1, 18 students scored above the Minimum Competency (KKM) for critical reading skills, with a critical reading skills percentage of 60. In cycle 2, 25 students scored above the Minimum Competency (KKM) for critical reading skills, with a critical reading skills percentage of 83.3%.